THE NORMATIVE AND LOGICAL-STRUCTURAL FUNCTIONS OF PUNCTUATION IN SCIENTIFIC DISCOURSE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the normative and logical-structural functions of punctuation in scientific discourse. It argues that punctuation in academic texts serves not only as a formal grammatical mechanism but also as a system that ensures logical coherence, semantic precision, and hierarchical organization of scientific information. Using discourse-analytic and syntactic approaches, the study demonstrates how punctuation contributes to clarity, argument structure, and epistemic reliability in scientific writing.